AUTOMATION OF WEIGHT EXPERIMENT IN UTAD-2 AERODYNAMIC PIPE - Волинська, Л. Г.; Виноградський, П. М. (Proceedings of National Aviation University (archive), 2021)
The structure, operational properties and metrological characteristics of the information and computer system of the UTAD-2 windpipe are considered. The results of calibration of measuring equipment, methods of weight tests are given. The achieved accuracy of determination of aerodynamic coefficients is shown.